THE EFFECT OF INFLATION, EXCHANGE, INTEREST RATES, AND WORLD CRUDE OIL PRICES ON JAKARTA ISLAMIC INDEX AND ITS IMPLICATION AGAINST DEVELOPMENT OF PORTFOLIO INVESTMENT IN INDONESIA, PERIOD 2004-2015 - Mr Yulianto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
The Jakarta Islamic Index is expected to increase investor confidence in developing Islamic investment. This study uses a quantitative, panel data and regression analysis. The results of the analysis show that the independent variables have a influence on the changes in the Jakarta Islamic Index (Y). While the independent variables that have a real effect on changes in Portfolio Investment (Z) through the Jakarta Islamic Index (Y) variable are the variables of inflation, the exchange rate of Rupiah and the world crude oil price. However, the Interest Rate variable does not have a real effect on changes in Portfolio Investment. The results of the combined coefficient of determination of structural equations obtained a value of 89%, meaning that the information contained can be explained by the model formed, while the rest, which is equal to 11% percent is explained by other variables.